The Process Of Creating Partial Reduplication Malay Dialect Of Urak Lawoi Lipek Island - Chapakiya, Suraiya (Al-HIKMAH Journal, 2018)
This research discusses the process of creating partial reduplication Malay Dialect of Urak Lawoi Lipek Island (MDULLI). The objective of this study is to analyse the process of creating partial reduplication process within the MDULLI. This data collection, the researcher interview with 10 respondents above the age of 50 years old from Lipek Island, Satun. This data was processed and analysed using the autosegmental theory which is based on the model of the melodic transfer by Clements (1985) and Clement’s Representation Level of Syllable Structure (1985). The process of creating partial reduplication data of MDULLI was processed with KVK template. The finding of the MDULLI has two types of partial reduplication which is the partial reduplication that ending with an open syllable such as /sama/ [sa.ma)] [ma).sa.ma)] (simillar) and the partial reduplication that ending with a closed syllable such as /malam/ [ma).lap] [lap.ma).lap] (at night).